Correction: Understanding student perceptions of social computing and online tools to enhance learning. - Semiyu Adejare Aderibigbe; Wafa Barhoumi Hamdi; Khadeegha Alzouebi; William Frick; Assad Asil Companioni (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0276490.].